2015
DOI: 10.1634/theoncologist.2015-0138
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Biomarker Analysis of the Randomized CHER-LOB Study Evaluating the Dual Anti-HER2 Treatment With Trastuzumab and Lapatinib Plus Chemotherapy as Neoadjuvant Therapy for HER2-Positive Breast Cancer

Abstract: Background. The CHER-LOB randomized phase II study showed that the combination of lapatinib and trastuzumab plus chemotherapy increases the pathologic complete remission (pCR) rate compared with chemotherapy plus either trastuzumab or lapatinib. A biomarker program was prospectively planned to identify potential predictors of sensitivity to different treatments and to evaluate treatment effect on tumor biomarkers. Materials and Methods. Overall, 121 breast cancer patients positive for human epidermal growth fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(124 citation statements)
references
References 32 publications
(24 reference statements)
4
118
2
Order By: Relevance
“…This TP53 mutation frequency is higher than that published for primary breast cancer and the enrichment may reflect the fact that all the patients had stage IV disease at the time of sequencing and that TP53 missense mutation is a negative prognostic factor for breast cancer . The association between PIK3CA mutations in ERBB2 amp breast cancer and the development of resistance to anti‐HER2 targeted therapy is well documented . However, to the best of our knowledge, the association between PIK3CA mutations and ERBB2 mut in breast cancer is not well known and the potential impact of PIK3CA mutations on the treatment of patients with ERBB2 mut breast cancer is currently not known.…”
Section: Discussionmentioning
confidence: 78%
“…This TP53 mutation frequency is higher than that published for primary breast cancer and the enrichment may reflect the fact that all the patients had stage IV disease at the time of sequencing and that TP53 missense mutation is a negative prognostic factor for breast cancer . The association between PIK3CA mutations in ERBB2 amp breast cancer and the development of resistance to anti‐HER2 targeted therapy is well documented . However, to the best of our knowledge, the association between PIK3CA mutations and ERBB2 mut in breast cancer is not well known and the potential impact of PIK3CA mutations on the treatment of patients with ERBB2 mut breast cancer is currently not known.…”
Section: Discussionmentioning
confidence: 78%
“…To this end, we selected genes with significantly negative CARE scores, indicating that high gene expression levels correlate with lapatinib resistance. We further selected genes upregulated in lapatinib-resistant cell lines (Bailey et al, 2014; Liu et al, 2009) and negatively associated with patient response in the CHER-LOB trial (Guarneri et al, 2015). Among the 47 genes meeting these criteria, only PRKD3 and AKT3 have compound inhibitors available (Table S5A).…”
Section: Resultsmentioning
confidence: 99%
“…The gene expression profiles of pre-treatment tumors and patient clinical information were collected for vemurafenib in melanoma (Hugo et al, 2015), lapatinib in HER2+ breast cancer (Guarneri et al, 2015), pembrolizumab in melanoma (Hugo et al, 2016), and paclitaxel in breast cancer (Hatzis et al, 2011; Miyake et al, 2012; Popovici et al, 2010). In each dataset, the expression value of each gene is normalized by subtracting the mean value across all samples.…”
Section: Star Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [33] found that the PI3K pathway activation resulting from PTEN loss or PIK3CA mutations leads to drug resistance to lapatinib and Tmab in metastatic breast cancer. In the neoadjuvant setting, patients with HER2-positive breast cancer who harbor a PIK3CA mutation are less likely to benefit from the combination of Tmab plus lapatinib [34]. Therefore, PIK3CA mutations may serve as predictive biomarkers to help in selecting appropriate treatment choices.…”
Section: Discussionmentioning
confidence: 99%